Bilobate leaves of Bauhinia (Leguminosae, Caesalpinioideae, Cercideae) from the middle Miocene of Fujian Province, southeastern China and their biogeographic implications. (December 2015) - Lin, Yanxiang; Wong, William; Shi, Gongle; Shen, Si; Li, Zhenyu
Abstract Background Morphological and molecular phylogenetic studies suggest that the pantropical genusBauhinia L. s.l. (Bauhiniinae, Cercideae, Leguminosae) is paraphyletic and may as well be subdivided into nine genera, includingBauhinia L. s.s. and its allies. Their leaves are usually characteristic bilobate and are thus easily recognized in the fossil record. This provides the opportunity to understand the early evolution, diversification, and biogeographic history of orchid trees from an historical perspective under the framework of morphological and molecular studies. Results The taxonomy, distribution, and leaf architecture ofBauhinia and its allies across the world are summarized in detail, which formed the basis for classifying the bilobate leaf fossils and evaluating the fossil record and biogeography ofBauhinia . Two species ofBauhinia are described from the middle Miocene Fotan Group of Fujian Province, southeastern China.Bauhinia ungulatoides sp. nov. is characterized by shallowly to moderately bilobate, pulvinate leaves with shallowly cordate bases and acute apices on each lobe, as well as paracytic stomatal complexes.Bauhinia fotana F.M.B. Jacques et al. emend. possesses moderately bilobate, pulvinate leaves with moderately to deeply cordate bases and acute or slightly obtuse apices on each lobe. Conclusions Bilobate leaf fossilsBauhinia ungulatoides andB. fotana together with other late Paleogene – early Neogene Chinese record of the genus suggest thatBauhinia had been diverse in South China by the late Paleogene. Their great similarities to some species from South America and South Asia respectively imply thatBauhinia might have undergone extensive dispersals and diversification during or before the Miocene. The fossil record, extant species diversity, as well as molecular phylogenetic analyses demonstrate that the Bauhiniinae might have originated in the Paleogene of low-latitudes along the eastern Tethys Seaway. They dispersed southwards into Africa, migrated from Eurasia to North America via the North Atlantic Land Bridge or floating islands during the Oligocene. Then the genus spread into South America probably via the Isthmus of Panama since the Miocene onward, and underwent regional extinctions in the Boreotropics of mid-high-latitudes during the Neogene climatic cooling. Hence, Bauhinia presently exhibits a pantropical intercontinental disjunct distribution.